Anadromous Fish Enhancement and Restoration: 2002 Annual Performance Report - Gephard, S; Wildman, T; Ravita, J; Williams, B; Ellis, D (ScholarWorks@UMass Amherst, 2003)
From executive summary: The purpose of this project is to restore and enhance anadromous fish runs to the streams of Connecticut through the construction and operation of fishways and the reintroduction of fish into selected watercourses. The goals of this project are to: (1) Restore Atlantic salmon to selected tributaries of the Connecticut River Basin. (2) Restore and enhance runs of American shad in selected streams. (3) Restore and enhance runs of alewife and blueback herring in selected streams. (4) Provide effective fish passage at existing fish passage facilities. (5) Provide effective fish passage at existing barriers to fish migration. (6) Keep the public informed on the efforts to manage anadromous fish resources. (7) Engage in activities essential to the professional management of anadromous fish resources.